A Dual-Mode Detection Sensor Based on Nitrogen-Doped Carbon Dots for Visual Detection of Fe(III) and Ascorbic Acid via a Smartphone - Kayani, Kawan F.; Abdullah, Chalak Najat (Journal of fluorescence, 2025)
Accurately and promptly detecting Fe 3+ and ascorbic acid (AA) is a crucial objective. In this study, nitrogen-doped carbon dots (N-CDs) were synthesized using a one-step hydrothermal synthesis method with 6,9-diamino-2-ethoxyacridine lactate as the precursor. The introduction of Fe 3+ and AA resulted in both fluorescence (FL) quenching and enhancement of the synthesized N-CDs. The fluorescent response of the N-CDs probe to Fe 3+ was observed in the concentration range of 5–20 µM and 25–50 µM, with a limit of detection (LOD) of 290 nM. Remarkably, the fluorescence of the N-CDs was recovered upon the addition of AA to the N-CDs-Fe 3+ system. Using the “off-on” fluorescent N-CDs probe, a linear range of 40–90 µM was achieved with an LOD of 0.69 µM. Additionally, the feasibility of employing a smartphone equipped with an RGB Color Picker was demonstrated for the analysis of Fe 3+ and AA concentrations, providing a novel visual detection method. Furthermore, the application of N-CDs in solution demonstrated considerable potential for visually detecting Fe 3+ and AA. The proposed dual-mode detection sensor was found to be simple, efficient, and stable, enabling the successful determination of Fe 3+ and AA in practical samples with satisfactory results. Graphical Abstract